Revitalisasi Nilai-Nilai Hindu dalam Tradisi Nyepi: Strategi Ketahanan Budaya dan Spiritual di Tengah Krisis Global - Sepi Wahyuni, Ni Wayan; Suastika, I Nengah; Adhi Utami, Anak Agung Istri; Yanti, Putu Risma; Apriani, Ni Komang; Purnama Dewi, Ni Putu Sri Wahyuni; Sriwidiani, Ni Putu Eka; Sucitra, Ni Kadek Ayuatik (Ganesha Civic Education Journal, 2025)
The Nyepi tradition, celebrated as the Saka New Year in Balinese Hinduism, functions not only as a religious ritual but also as a reflective space filled with philosophical, theological, and socio-cultural values. In the midst of global crises such as climate change, pandemics, and declining spiritual awareness, Nyepi has emerged as a cultural strategy that strengthens the spiritual and cultural resilience of Balinese society. This study examines how Hindu values—tapa, brata, yadnya, and moksha—are contextually revitalized to address contemporary global challenges. Using qualitative methods with hermeneutic and phenomenological analysis, data were gathered through literature review, participant observation during the Nyepi series (Tawur Agung, Catur Brata Penyepian, and Ngembak Geni), and interviews with religious leaders, cultural practitioners, and community members. The findings show that Nyepi is increasingly understood as a collective contemplative moment that cultivates eco-spiritual awareness. Practices of silence, fasting, and voluntary isolation act as forms of resistance to consumerism and global noise while fostering deeper spiritual solidarity. Revitalized Hindu values also appear through digital media engagement, environmental movements, and their integration into educational settings. Thus, Nyepi becomes a spiritual-ecological model that highlights harmony between humans, nature, and the transcendent, offering a framework for a globally relevant public theology within Balinese Hinduism